PENGARUH MODEL KOOPERATIF TIPE TARI BAMBU TERHADAP HASIL BELAJAR IPS DI SD - Pebrianita, Repa; Asran, Mastar; Kresnadi, Hery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research has purpose to examine the influence of applying cooperatif model bamboo dancing type on academic achievement of social science elementary school students fourth grade at SDN 68 Pontianak Barat. Experimental research method has been employed. Quasi eksperimental design and nonequivalent control group design has been used. 157 students in fourth grade of SDN 68 Pontianak Barat has been the population of this research. Measurement technique has been used. 40 Multiple choice questions are used as the data collect instrument. Based on the analysis of t-test the t value = 5,0310 and t table= ( = 5%) = 1,998 and it has shown if there is influence of applying cooperatif model bamboo dancing type in the academic achievement of social science subject. It is also find that the effect size =0,88( high level). As has been mentioned before, The usage of cooperatif model bamboo dancing type influence the academic achievement of social science elementary school students grade four at sekolah dasar negeri 68 pontianak. Key words : influences, cooperatif model, bamboo dancing, academic achievement, social science.